Perspectives on grammar writing - Payne, Thomas Edward, 1951-; Weber, David, 1947- (Benjamins current topics, 2007)
With over half the languages of the world currently in danger of extinction within a century, the need for high quality grammatical descriptions is more urgent than ever. Potential grammar writers, however, often find themselves paralyzed by the daunting task of describing a language. The papers in the present volume (originally published in Studies in Language 30:2 (2006)) provide suggestions and encouragement - from experienced grammar writers and users - regarding concrete methods for approaching the task of writing a descriptive grammar of a language. Salient "themes" emerging from the pap.